Perilaku makan pelengkap pada ibu balita usia 6-24 bulan (belajar di Pingit, Bumijo, Yogyakarta) - Lili Indah Nurcahyani; Nanik Setiawati; Sabar Santoso (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
Malnutrition situation happened as the result of receiving less breast milk and diet on complementary feeding for toddlers. It is known that the practice of complementary feeding for age 6th month until 2 years has not been implemented properly. The purpose of this study is to reveal complementary feeding behavior on toddler’s mother age 6-24 months in Pingit, Bumijo, Jetis, Yogyakarta. The types of this study is descriptive study using cross sectional design. Population for this study are mother who have toddler in age of 6-24 months. The total for respondents for the sample is 78 respondents. Data collection techniques used in this study is questionnaire. Data Analysis for this study is using univariate. As for the result of this study, parity of multi-parent respondents represented in 51.3%, with medium education represented in 46.2%, doesn’t have job represented in 73.1%, and family income under minimum wage regional city of Yogyakarta represented in 51.3%. As for the complementary feeding behavior: first, the time accuracy is done by 67.9% respondents. Second, the frequency accuracy is done by 84.9% respondents. Third, the quantity accuracy is done by 47.4% respondents. Fourth, the texture accuracy is done by 17.9% respondents. Fifth, the variation accuracy is done by 53.8% respondents. The conclusion in this study is the complementary feeding behavior done based on time, frequency and variation and not exactly based on the quantity and texture.